PERAN PENDIDIKAN DALAM MENINGKATKAN HARMONISASI MASYARAKAT - Demi, Trawia Fitriani; la Cady, Siti Amina Novia Ramadani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze the strategic role of education in shaping social harmony in a plural society. Using a qualitative approach with library research methods, this study explores how educational institutions can internalize the values of tolerance, cooperation, and peace. Data sources were obtained from scholarly literature and relevant educational policies. The analysis shows that value-based education, the application of a multicultural curriculum, and the role of teachers as peace agents are key factors in creating an inclusive and harmonious society. Beyond being a medium of knowledge transfer, education serves as a means of character and social transformation that fosters empathetic, ethical, and peace-loving generations. These findings highlight the importance of comprehensive educational reform and multi-stakeholder collaboration in building an education system that upholds social justice and equality for all citizens. Keywords: education,tolerances, harmony,